Electronic structure and UV spectrum of hexachloroplatinate dianions in vacuo - Kaufman, Sydney H.; Weber, J. Mathias; Pernpointner, Markus (The journal of chemical physics, 2013)
We present a joint experimental and theoretical study of the electronic spectrum of hexachloroplatinate dianion. We have measured electronic photodissociation and photodetachment spectra of mass-selected PtCl62− ions in vacuo and compare these with calculated band positions from time-dependent density functional theory and from relativistic calculations. Excitation of an electronic transition of the dianion leads to resonant enhancement of the photodetachment cross section superimposed on direct detachment. Photoexcitation results in loss of Cl− and Cl0, depending on photon energy. The photofragmentation spectrum for formation of the PtCl4− fragment ion mirrors the UV/vis absorption spectrum of PtCl62− in solution with a small solvatochromic shift.